Analisis Produksi Padi Jawa Timur menggunakan Sistem Dinamik Mendukung Upaya Ketahanan Pangan - Rima Tsaniyah Amilatus Sholihah; Agung Brastama Putra; Seftin Fitri Ana Wati (STMIK Banjarbaru, 2024)
Indonesia, as a country with a rapidly developing agricultural sector, faces challenges in maintaining food security. Increasing population and limited agricultural land can cause a food crisis. Therefore, this study aims to provide relevant information regarding model development and simulation of paddy production in East Java. This study uses a dynamic system approach to describe the food needs of the people in East Java and support food security efforts. The results of this study are presented in the form of a Causal Loop Diagram (CLD) which provides an overview of the cause-and-effect relationships between variables in the system. By using CLD, this research visualizes the interaction of various factors that influence paddy production. In addition, this study produces three scenarios that focus on improving the quality of fertilizers, adding agricultural technology, and a combination of the two previous scenarios. This analysis helps to understand the factors that influence paddy production and provides insight into increasing paddy productivity in East Java.Keywords: Paddy Production Analysis; System Dynamics; Food Security; Causal Loop Diagram AbstrakIndonesia, sebagai negara yang memiliki sektor pertanian yang berkembang pesat, menghadapi tantangan dalam menjaga ketahanan pangan. Pertumbuhan populasi yang terus meningkat sementara lahan pertanian terbatas menimbulkan kekhawatiran akan krisis pangan. Oleh karena itu, penelitian ini bertujuan untuk menyediakan informasi yang relevan dalam pengembangan model dan simulasi produksi padi di Jawa Timur. Penelitian ini menggunakan pendekatan sistem dinamik untuk menggambarkan kebutuhan pangan masyarakat Jawa Timur dan mendukung upaya ketahanan pangan. Hasil penelitian ini adalah Causal Loop Diagram (CLD), yang memberikan gambaran tentang hubungan sebab-akibat antara variabel-variabel dalam sistem. Dengan menggunakan CLD, maka digambarkan interaksi antara berbagai faktor yang memengaruhi produksi padi. Selain itu, penelitian ini menghasilkan tiga skenario yang berfokus pada peningkatan kualitas pupuk, penambahan teknologi pertanian, dan kombinasi kedua skenario sebelumnya. Analisis ini membantu memahami faktor-faktor dan memberikan wawasan yang memengaruhi produksi padi di Jawa Timur.Kata kunci: Analisis Produksi Padi; Sistem Dinamik; Ketahanan Pangan; Causal Loop Diagram.